Assessment of Quality of Life (QoL) of Colorectal Cancer Patients using QLQ-30 and QLQ-CR 29 at King Abdulaziz Medical City, Jeddah, Saudi Arabia. (17th May 2022) - Qedair, Jumanah T.; Al Qurashi, Abdullah A.; Alamoudi, Saeed; Aga, Syed Sameer; Y. Hakami, Alqassem
Abstract : Objective . We aimed to assess the quality of life (QoL) and its predictors in colorectal cancer (CRC) patients at King Abdulaziz Medical City, Jeddah. Methods . A total of 118 CRC patients at King Abdulaziz Medical City, a tertiary hospital in Jeddah, participated in this study. The participants were provided with the online questionnaire via WhatsApp by trained researchers and data collectors in February 2021. All participants were required to answer the three-section questionnaire comprising of (a) demographic data and a validated Arabic version of the European Organization for Research and Treatment of Cancer (EORTC) quality of life questionnaires, (b) a general version (QLQ-30), and (c) a CRC-specific version (QLQ-CR29). Results . Statistical analysis revealed that the most common comorbidity among the participants was diabetes mellitus (42.4%). In addition, the mean global health status was 63.91 ± 24.75. For the global health tool QLQ-C30, results exhibited that physical functioning [62.94 (30.04)] and social functioning [63.56 (31.95)] scored below the threshold, while the cognitive functioning scale scored the highest [74.86 (25.11)]. In addition, on the QLQ-C30 scales, fatigue and insomnia were distressing, with fatigue scoring the highest. For the disease-specific tool QLQ-CR29, it was found that for the symptom scale, urinary frequency and embarrassment scored the highest. Conclusion. The participants reported high global quality of life on both the EORTC QLQ-30 and QLQ-CR29 scales. This study identifies the factors and predictors that affect the quality of life of CRC patients in Saudi Arabia. Recognizing these factors and predictors may empower those patients to maintain positive perception towards the impact of colorectal cancer and improve their survival.